Ketamine Attenuates Airway Inflammation via Inducing Inflammatory Cells Apoptosis and Activating Nrf2 Pathway in a Mixed-Granulocytic Murine Asthma Model - Xiao S; Zhou Y; Wang Q; Yang D (Dove Medical Press, 2022)
Shilin Xiao, Ying Zhou, Qianyu Wang, Dong Yang Department of Anesthesiology, Plastic Surgery Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Dong Yang, Department of Anesthesiology, Plastic Surgery Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, 33 Badachu Road, Shijingshan, Beijing, 100144, People's Republic of China, Tel +86-13661267522, Email yangdongpsh@163.comPurpose: The use of ketamine, an anesthetic, as a treatment for asthma has been investigated in numerous studies. However, how ketamine affects asthma is unclear. The present study examined the effects of ketamine on a murine model of mixed-granulocytic asthma, and the role of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway.Methods: The murine model of mixed-granulocytic asthma was established using ovalbumin (OVA) for sensitization and the combination of OVA and lipopolysaccharides (LPS) for challenge. The main characteristics of asthma, oxidative stress biomarkers, and the expression of the Nrf2 pathway were examined. ML385 was administered to verify the role of the Nrf2 pathway.Results: Mice in the OVA +LPS group developed asthmatic characteristics, including airway hyperresponsiveness, mixed-granulocytic airway inflammation, mucus overproduction, as well as increased levels of oxidative stress and impaired apoptosis of inflammatory cells. Among the three concentrations, ketamine at 75mg/kg effectively attenuated these asthmatic symptoms, activated the Nrf2 pathway, decreased oxidative stress, and induced apoptosis of eosinophils and neutrophils in bronchoalveolar lavage fluid (BALF) with a reducing level of myeloid cell leukemia 1(Mcl-1). ML385 (an Nrf2 inhibitor) eliminated the protective effects of ketamine on the mixed-granulocytic asthma model.Conclusion: The study concluded that ketamine reduced oxidative stress and attenuated asthmatic symptoms (neutrophilic airway inflammation) by activating the Nrf2-Keap1 pathway, with 75 mg/kg ketamine showing the best results. Ketamine administration also increased neutrophil and eosinophil apoptosis in BALF, which may contribute to the resolution of inflammation. The use of ketamine as a treatment for asthma may therefore be beneficial.Keywords: ketamine, asthma, inflammation, apoptosis, oxidative stress, NF-E2-related factor 2